Oral and colonic microbiomes and colon cancer - Vitorino dos Santos (Shiraz University of Medical Sciences, 2021)
Oral microbiota include bacteria, fungi, protozoa, and viruses, which can translocate via the digestive tract and may favor local benign or malignant pathology development. Some researchers have studied the physiopathological mechanisms involving the role of oral microorganisms in intestinal diseases. Two significant areas of these studies are colorectal cancer and coronavirus disease 2019 (COVID-19). Some of the intestinal manifestations of this pandemic may be associated with dysbiosis. Both synergistic and antagonistic bacterial and fungal associations have been described in patients with colorectal cancer, characterizing dysbiosis. Oral microbes can cause opposing effects to the beneficial intestinal flora, eliciting DNA epithelial damage and apoptosis in the bowel as tumor triggering factors. Increased levels of Fusobacterium nucleatum and Porphyromonas gingivalis have been found in association with colorectal cancer. The recent advent of new biomarkers to diagnose colorectal tumors is also considered. The aim of these comments is to emphasize the usefulness of the more recent findings.